PiWall as a home traffic controller: enabling parental control and monitoring - Abd Razak, Nurul Imanina; Kamarudin, Shafinah; Shuhud, Mohd Ilias M.; Zakaria, Muhammad Luqman Mahamad; Mohd, Siti Munirah; Wahab, Amelia Natasya Abdul (Bulletin of Electrical Engineering and Informatics, 2024)
The movement control order (MCO) has led to a surge in internet usage among children, becoming the new normal. Most countries heavily rely on online platforms for education, granting children more freedom to explore the internet using electronic devices. Yet, it is challenging for parents to monitor their online activities. Children may stumble upon unsuitable content such as pornography or get redirected to harmful websites through pop-up advertising. To address these concerns, this study proposes PiWall, a home traffic controller. PiWall aims to block undesirable websites and filter out advertisements to help parents manage their home network. Testing shows that PiWall significantly improves the internet browsing experience by reducing website loading times and network traffic, hence offering protection against inappropriate content and malicious attacks. Implementing PiWall as a home traffic controller is a viable alternative to traditional parental controls in creating a safer internet environment for children.